Analisis Kesehatan Keuangan Perusahaan Jasa Infrastruktur Berdasarkan Surat Keputusan Menteri BUMN Nomor: KEP-100/MBU/2002 (Periode 2017-2021) - Dasu, Wahyudi Tri; Wiyono, Gendro; Maulida, Alfiatul (Ekonomis: Journal of Economics and Business, 2024)
This study aims to find out about financial performance in assessing the soundness level of the financial aspects of Infrastructure Service Companies for the 2017-2021 period based on the decree of the minister of BUMN Number: KEP-100/MBU/2002 concerning the assessment of the soundness level of BUMN in this assessment using eight indicators, namely Return On Equity (ROE), Return On Investment (ROI), cash ratio, current ratio, collection periods, investory turnover, total asset turn over (TATO), and total own capital to total asset. The financial performance of infrastructure service companies for the 2017-2021 period has increased and decreased when viewed from a total score of eight financial ratio indicators during 2017-2018 infrastructure service companies have experienced increases and decreases for the level financial soundnes of infrastructure service companies are as follows in 2017 the total score 30,2 getting unhealthy predicate with category B, in 2018 a total score 21,7got an unhealthy predicate with the CCC categoty, in 2019 a totel score of 23,2 7got an unhealthy predicate with the CCC categoty, in 2020 a total score of 24 7got an unhealthy predicate with the CCC categoty, and finaly in 2021 a total score of 22,5 7got an unhealthy predicate with the CCC categoty.